Sliding member
The resin coating layer with specific thickness and roughness enhances fatigue and abrasion resistance in sliding members by addressing stress concentration and base layer exposure issues.
Patent Information
- Application Number
- JP2019019802
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2019-02-06
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2039-02-06
AI Technical Summary
Existing sliding members face issues with fatigue resistance and abrasion resistance due to stress concentration at the upper end of the metal sintering layer, which can lead to exposure of the base layer when the resin coating is too thin, and insufficient protection when too thick.
A resin coating layer with a thickness of more than 20 μm and surface roughness of 60 μm or less is applied, supporting the base material without exposing the metal sintering layer, using a resin composition with specific additives to enhance fatigue and abrasion resistance.
The solution improves fatigue and abrasion resistance by reducing stress concentration and preventing exposure of the base layer, while maintaining effective sliding performance.
Smart Images

Figure 0007626380000002 
Figure 0007626380000003 
Figure 0007626380000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a slide member. [Background technology]
[0002] A sliding member in which a resin coating layer is formed on the surface of a backing metal to improve the characteristics of the sliding surface is known. For example, Patent Document 1 describes a sliding member that uses a PAI resin as a binder resin and graphite as a solid lubricant. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 5683571 Summary of the Invention [Problem to be solved by the invention]
[0004] In the sliding member of the cited document 1, a metal sintered layer is formed on the surface of the base layer in order to improve the adhesion between the resin coating layer and the base layer (backing metal). However, in such a sliding member, stress is concentrated at the upper end portion of the metal sintered layer, which results in a problem of a decrease in fatigue strength of the resin coating layer. One method of improving fatigue strength is to make the resin coating layer thinner, but if the resin coating layer is too thin, there is a problem that the resin coating layer wears away with use, exposing the base layer.
[0005] In response to this, the present invention provides a technique for improving the fatigue strength and wear resistance of a sliding member. [Means for solving the problem]
[0006] The present invention provides a slide member comprising a substrate having a shape with a surface for supporting a counter material, the substrate having no exposed metal sintered layer on the surface, and a resin coating layer having a thickness exceeding 20 µm formed on the inner circumferential surface.
[0007] The resin coating layer may have a thickness of more than 50 μm.
[0008] The resin coating layer may have a thickness of 300 μm or less.
[0009] The surface roughness of the face may be 60 μmRzJIS or less.
[0010] The counter member may be a shaft, and the base material may have a cylindrical shape having an inner circumferential surface for supporting the shaft.
[0011] The inner circumferential surface may have a surface roughness in an axial direction of the mating shaft greater than a surface roughness in a circumferential direction of the mating shaft. Effect of the Invention
[0012] According to the present invention, the fatigue strength and wear resistance of a sliding member can be improved. [Brief description of the drawings]
[0013] [Figure 1] 1 is a diagram illustrating an example of the appearance of a bushing 1 according to an embodiment; [Diagram 2] FIG. 2 is a diagram illustrating a cross-sectional structure of a bush 1. [Diagram 3] 2A to 2C are diagrams illustrating the surface structures of a main body 11 and a resin layer 13. [Figure 4] FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] 1. Configuration FIG. 1 is a diagram illustrating an example of an external appearance of a bushing 1 according to an embodiment. The bushing 1 is an example of a sliding member according to the present embodiment. The bushing 1 is used, for example, in a fuel injection pump. The bushing 1 has a main body 11. The main body 11 has a cylindrical shape having an inner circumferential surface for supporting a mating shaft 9 (an example of a mating material). The main body 11 is formed, for example, of a metal (specifically, steel, cast iron, an aluminum alloy, a copper alloy, or the like) in order to ensure the strength and reliability required as a part. The main body 11 may be formed of a single layer of metal, or may be formed of multiple layers of metal (for example, a backing metal and a lining layer).
[0015] FIG. 2 is a diagram illustrating a cross-sectional structure of the bushing 1. FIG. 2 shows a cross section perpendicular to the sliding surface. The bushing 1 has a main body 11 (an example of a base material or backing metal) and a resin layer 13 (an example of a resin coating layer). In some types of bushings, a sintered layer made of metal (e.g., copper or copper alloy) powder is formed on the surface of the base material that serves as the base for the resin layer, but the bushing 1 according to this embodiment does not have a sintered layer (the metal sintered layer is not exposed). By not having a sintered layer, it is possible to reduce stress concentration at the upper end portion of the sintered layer of the resin layer, and thus to improve fatigue strength.
[0016] Instead of having a sintered layer, the surface of the body 11 on which the resin layer 13 is formed is subjected to a roughening treatment. From the viewpoint of reducing stress concentration in the surface shape, the surface roughness of the surface on which the resin layer 13 is formed is, for example, 60 μmRzJIS or less, preferably 30 μmRzJIS or less, and more preferably in the range of 5 μmRzJIS or more and 10 μmRzJIS or less.
[0017] In order to prevent the resin layer 13 from peeling off from the main body 11 due to shear stress when the mating shaft 9 makes one-sided contact (the mating shaft 9 contacts the sliding surface while tilted relative to the sliding surface), it is preferable that the surface roughness in the axial direction of the mating shaft 9 be greater than the surface roughness in the circumferential direction.
[0018] The resin layer 13 is formed of a resin material for sliding members. This resin material includes a binder resin 131 and an additive 132 dispersed in the binder resin 131. For example, a thermosetting resin, more specifically, at least one of a polyimide (PI) resin and a polyamide-imide (PAI) resin, is used as the binder resin 131. From the viewpoint of improving fatigue resistance, it is preferable to use a PI resin rather than a PAI resin, and it is preferable to use a high-strength PI resin (here, "high strength" refers to a tensile strength of 150 MPa or more). From the viewpoint of improving fatigue resistance, it is preferable that the content of the binder resin in the resin layer 13 is high, for example, preferably 80% by volume or more, more preferably 83% by volume or more, even more preferably 85% by volume or more, and even more preferably 90% by volume or more.
[0019] The additive 132 is a substance for improving the characteristics of the resin layer 13, and includes, for example, at least one of a solid lubricant 1321, a hard material (hard particles) 1322, and a silane coupling agent (the silane coupling agent is not shown). The solid lubricant 1321 is an additive for reducing the friction coefficient of the resin layer 13, and includes, for example, at least one of graphite and MoS2. Since MoS2 may tend to aggregate in the resin layer, it is preferable to use graphite as the solid lubricant 1321 and not use MoS2. When graphite is used as the solid lubricant 1321, it is preferable that the graphitization degree is high from the viewpoint of reducing the friction coefficient, for example, 95% or more, and more preferably 99% or more. The hard material 1322 is a substance for improving the seizure resistance and wear resistance of the resin layer 13, and includes, for example, at least one of clay, mullite, and talc. The silane coupling agent is a substance for strengthening the bond between the binder resin 131 and the solid lubricant 1321.
[0020] From the viewpoint of improving fatigue resistance, the content of additives is preferably low, for example, preferably 20 vol% or less in total, more preferably 17 vol% or less, even more preferably 15 vol% or less, and even more preferably 10 vol% or less. From the viewpoint of reducing the friction coefficient, the content of solid lubricant is preferably high, for example, 9 vol% or more. From the viewpoint of reducing the total amount of additives, the content of solid lubricant is preferably low, for example, 18 vol% or less. From the viewpoint of improving seizure resistance and wear resistance, the content of hard material is preferably high, for example, 0.5 vol% or more. From the viewpoint of reducing the total amount of additives, the content of solid lubricant is preferably low, for example, 3 vol% or less. In order to add both solid lubricant and hard material, the content of solid lubricant is preferably 9 vol% or more and 17 vol% or less, more preferably 14 vol% or less. The content of hard material is preferably 0.5 vol% or more and 3 vol% or less. The content of the silane coupling agent is preferably, for example, 0.1% by weight or more, more preferably 0.2% by weight or more, based on the binder resin. From the viewpoint of cost reduction, the content of the silane coupling agent is preferably, for example, 5% by weight or less, more preferably 3% by weight or less, based on the binder resin.
[0021] From the viewpoint of reducing surface roughness after cutting, it is preferable that the particle size of the additive 132 used as a material is small, and for example, the average particle size of the additive 132 is preferably smaller than the average particle size of the metal powder used in the sintered layer 12. Furthermore, it is preferable that the average particle size of both the solid lubricant 1321 and the hard material 1322 is 5 μm or less or less than 5 μm, and more preferably 3 μm or less or less than 3 μm.
[0022] Since the resin layer 13 is used as a sliding member, the fatigue resistance strength, i.e., fatigue surface pressure, is preferably 50 MPa or more, more preferably 80 MPa or more, and even more preferably 90 MPa or more. The method for measuring the fatigue surface pressure will be described later. From the viewpoint of improving the fatigue resistance of the resin layer 13, it is preferable that the average particle size of the solid lubricant 1321 used as a material is small, for example, it is preferably not more than twice the average particle size of the hard material 1322, and more preferably it is smaller than the average particle size of the hard material 1322.
[0023] It is believed that an increase in the content of the additive 132 in the resin layer 13 reduces the fatigue resistance of the resin layer 13. In this embodiment, the fatigue resistance is improved by reducing the content of the additive.
[0024] FIG. 3 is a diagram illustrating the surface structure of the main body 11 and the resin layer 13. Like FIG. 2, FIG. 3 shows a cross section perpendicular to the sliding surface. In order to prevent the resin layer 13 from wearing away and exposing the base layer (main body 11) as the bushing 1 is used, the thickness of the resin layer 13 is preferably greater than 20 μm, more preferably greater than 50 μm, and even more preferably greater than 100 μm. From the viewpoint of improving fatigue strength and seizure resistance, the thickness of the resin layer 13 is preferably 300 μm or less. The thickness T of the resin layer 13 refers to the length from the highest point of the unevenness on the surface of the main body 11 to the highest point on the surface of the resin layer 13, as shown in FIG. 3.
[0025] 2. Working Example The inventors of the present application prepared test pieces of the sliding member under various conditions and evaluated the characteristics of the resin layer 13 of these test pieces.
[0026] 2-1. Preparation of test specimens A steel plate (SPCC (JIS)) with a thickness of 1.5 mm was used as the substrate. In Experimental Example 1, the substrate surface was roughened by sanding. The surface roughness after roughening was 20 to 60 μmRzJIS. In Experimental Examples 2 and 3, copper alloy powder (average particle size 100 μm) was scattered on the substrate to a thickness of 100 μm, and then sintered by heating to 930°C in a reducing atmosphere without pressing. For these samples, a precursor solution for forming a resin layer having the composition in Table 1 was prepared, and this precursor solution was applied onto the sintered layer by a knife coating method. After application, the sample was dried for about 60 to 90 minutes at a temperature range of room temperature to about 200°C. The sample was then heated to about 300°C and fired for about 30 to 90 minutes.
[0027] [Table 1]
[0028] In Experimental Examples 1 and 2, graphite with an average particle size (volume-based d50) of 1.5 μm and a graphitization degree of 99% was used. In addition, high-strength PI resin with a tensile strength of 195 MPa, elongation of 90%, elastic modulus of 3.8 GPa, and glass transition temperature Tg of 285°C was used. In Experimental Example 3, graphite with an average particle size of 12.5 μm and a graphitization degree of 90% was used. MoS2 with an average particle size of 1.5 μm was used. Furthermore, PI resin with a tensile strength of 119 MPa, elongation of 47%, and glass transition temperature Tg of 360°C, and PAI resin with a tensile strength of 112 MPa, elongation of 17%, elastic modulus of 2.7 GPa, and glass transition temperature Tg of 288°C were used. In Experimental Examples 1 and 2, silane coupling agent with the chemical formula 3(H3CO)SiC3H6-NH-C3H6Si(OCH3)3 was used. In addition, the content of the silane coupling agent is shown as a weight ratio to the high-strength PI resin in Table 1. In Experimental Examples 1 to 5, the clay used had the structural formula Al2O3·2SiO2 and an average particle size of 3 μm.
[0029] In Experimental Examples 1 and 2, only graphite was used as the solid lubricant (i.e., no other solid lubricants such as MoS2 were used). In addition, no additives were used other than the solid lubricants, hard materials, and silane coupling agents shown in Table 1. All of the additives had an average particle size of 3 μm or less.
[0030] 2-2.Abrasion test Abrasion tests were carried out on the test pieces of Experimental Examples 1 to 3. The abrasion tests were carried out under the following conditions, and the abrasion depth after the tests was recorded. Testing machine: Box bush testing machine Surface pressure: 1.8MPa Test pattern: Run & Stop (100,000 cycles) Lubricant: Kerosene (room temperature)
[0031] 4 is a diagram showing the results of the wear test. Compared with Experimental Example 3, the wear depth was reduced to half or less in Experimental Examples 1 and 2. In other words, compared with Experimental Example 3, the wear resistance was improved in Experimental Examples 1 and 2.
[0032] 2-3.Fatigue testing A fatigue test was carried out on the test pieces of Experimental Examples 1 to 3. The fatigue test was carried out under the following conditions, and the maximum contact pressure at which fatigue did not occur in the resin layer (maximum contact pressure of the test machine was 100 MPa) was defined as the fatigue contact pressure. Testing machine: Reciprocating dynamic load testing machine Rotational speed: 3000 rpm Number of repetitions: 105 Test temperature: 100℃ (lubricant supply temperature) Counterpart material: S45C Lubricant: Engine oil
[0033] The fatigue surface pressure resistance of Experimental Example 3 was 20 MPa, whereas the fatigue surface pressure resistance of Experimental Example 1 was 110 MPa or more, and the fatigue surface pressure resistance of Experimental Example 2 was 80 MPa. Compared with Experimental Example 3, the fatigue surface pressure resistance of Experimental Examples 1 and 2 was improved. Also, compared with Experimental Example 2, the fatigue surface pressure resistance of Experimental Example 1 was improved.
[0034] 2-4.Seizure test A seizure test was carried out on the test pieces of Experimental Example 1 and Experimental Example 2. The seizure test was carried out under the following conditions, and the surface pressure at which seizure occurred was defined as the seizure surface pressure. Testing machine: Static load seizure testing machine Load: Step up 1kN / 5min - Revolution speed: 6000rpm Lubricant: Paraffin oil
[0035] As a result of this test, the seizure surface pressure in Experimental Example 1 was 40 MPa, and the seizure surface pressure in Experimental Example 2 was 32 MPa. Thus, compared with Experimental Example 2, the seizure resistance was improved in Experimental Example 1. Regarding the state of the sliding surface after the test, the resin layer was damaged in all cases, but the back metal was not exposed. That is, even in Experimental Example 1, the resin layer did not peel off and the back metal was not exposed.
[0036] In addition, the adhesion strength between the main body and the resin layer was tested for Experimental Example 1 and Experimental Example 2. Both had adhesion strengths greater than or equal to the strength of the adhesive used in the tests, and no difference in adhesion strength was observed within the range of test conditions.
[0037] 3. Variations The various materials and their compositions used in the above-mentioned embodiments are merely examples, and the present invention is not limited thereto. The resin material according to the present invention may contain unavoidable impurities. The application of the bush 1 is not limited to that used as a bush in a fuel injection pump, and may be used in various bearings, compressors, etc. Furthermore, the sliding member according to the present invention is not limited to the bush 1, and the present invention may be applied to other sliding members such as a half bearing or a swash plate. [Explanation of symbols]
[0038] 1…Bush 11...Main body 13...Resin layer 131...Binder resin 132...Additives
Claims
1. A substrate having a shape having a surface for supporting a counter member, the metal sintered layer not being exposed on the surface; A resin coating layer having a thickness of more than 100 μm formed on the surface; having The resin coating layer is The tensile strength is 150 MPa or more, and the binder resin contains 80% by volume or more of a polyimide resin, The additives dispersed in the binder resin include graphite, clay, and a silane coupling agent; The graphite content is 9 volume % or more and 18 volume % or less, The clay content is 0.5% by volume or more and 3% by volume or less, The total content of the additives is 20% by volume or less, The polyimide resin contains 0.2% by weight or more and 5% by weight or less of a silane coupling agent, A sliding member having a surface roughness of 20 to 60 μm Rz JIS, In a fatigue test for measuring a fatigue resistance surface pressure, which indicates strength against fatigue caused when a load is repeatedly applied to the resin coating layer of the sliding member, Under the conditions that the test machine is a reciprocating dynamic load test machine, the rotation speed of the reciprocating dynamic load test machine is 3000 rpm, the number of repeated load applications is 105, the lubricant supply temperature representing the test temperature is 100° C., the mating material of the sliding member is S45C, and the lubricant is engine oil, When the maximum surface pressure in a state where no fatigue occurs in the resin coating layer is defined as the fatigue resistance surface pressure, The fatigue resistance surface pressure of the resin coating layer exceeds 100 MPa. Sliding member.
2. The thickness of the resin coating layer is 300 μm or less. The sliding member according to claim 1 .
3. The counter member is a shaft, The base material has a cylindrical shape having an inner peripheral surface for supporting the shaft. The sliding member according to claim 1 or 2.
4. On the inner peripheral surface, a surface roughness in an axial direction of the shaft is greater than a surface roughness in a circumferential direction of the shaft. The sliding member according to claim 3 .
Citation Information
Patent Citations
Apparatus for controlling current supply to glow plug
JP1981083571A
Sliding member
JP1989016842A
Rotary apparatus
JP2012055088A
Bearing and fuel injection pump
JP2016142287A
Resin material for sliding member and sliding member
JP2018193519A